This poem XXXII from Trilce, this poem: (A profane disgressions) - Gavidia Ruiz , Ángel (Espergesia, 2017)
This article analyses Trilce’s poem XXXII, which the author selects because at first sight it could very well illustrate the concept that young Ribeyro had about this collection of poems: a mockery, a provocation. The author resorts to two first-hand documents: the letter that Cesar Vallejo wrote to Antenor Orrego about Trilce’s appearing in Lima’s literary environment and the prologue to Trilce written precisely by Orrego, a very close companion to Vallejo’s creative  process. The author also uses Víctor Raúl Haya de la Torre and Orrego´s testimonies regarding a pertinent circumstance. The author has tried, as far as possible, to approach the poem as Orrego himself advises: “And you too, reader, are going to present yourself naked, abandoning your literary trapillo (clothing), to get to the poet. If you know something, act as if you knew nothing; the emotional and rhythmic virginity of “Trilce” refuses to be possessed by the presumptuous arrogance of the ‘know-it-all’”. The author concludes that Trilce’s poem XXXII poetizes the circumstance of an extenuating summer perceived and suffered from a room.